General strategy for a short and efficient synthesis of 3-hydroxy-4-methylprolines (HMP) - Mohapatra, Debendra K.; Mondal, Dhananjoy; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The non-proteinogenic amino acid 3-hydroxy-4-methylproline (HMP) is an active constituent of some potent antimicrobials including echinocandins, nostopeptins, pneumocandins, sporiofungin and mulundocandins. A synthesis has been achieved in 10 steps with 29% overall yield; the Evans' aldol reaction using Crimmins' modified method was pivotal to the success of the strategy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 3; 4-disubstituted proline; Crimmins' aldol reaction; Garner's aldehyde; non-proteinogenic amino acids; RUO4 mediated oxidation

Synthesis of the spiro fused beta-lactone-gamma-lactam segment of oxazolomycin - Mohapatra, Debendra K.; Mondal, Dhananjoy; Gonnade, Rajesh G.; Chorghade, Mukund S.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
An effective synthetic strategy for construction of the novel spiro-bicyclic beta-lactone-gamma-lactam system present in oxazolomycin has been demonstrated. The 3,4-disubstituted pyrrolidine ring system was constructed via an Evans aldol reaction. The spiro-beta-lactone ring was elaborated from a gem-hydroxymethyl moiety that was successfully installed by an aldol followed by a crossed Cannizzaro reaction. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: crossed Cannizzaro reaction; Evans' aldol reaction; Garner's aldehyde; intramolecular Mitsunobu reaction; ruthenium tetroxide oxidation

Concise synthesis of (2S,3S,4S)-2-(Hydroxymethyl)pyrrolidine-3,4-diol (LAB1) - Upadhyay, Puspesh K.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
The synthesis of (2S,3S,4S)-2-(hydroxymethyl)pyrrolidine-3,4-diol (LAB1) from Garner's aldehyde is described using the Sharpless asymmetric dihydroxylation as the key step.
Keywords: alkaloid; azasugars; diastereoselectivity; Garner's aldehyde; pyrrolidine; Wittig reaction

Synthetic view of an analogue of the spiro-beta-lactone-gamma-lactam ring in oxazolomycins and lajollamycin - Mondal, Dhananjoy; Bera, Smritilekha (Synthesis-Stuttgart, 2010)
Herein, we describe a new synthetic strategy towards an analogue of the spiro-beta-lactone-gamma-lactam ring found in a class of potent antibiotics, the oxazolomycins and lajollamycin. The synthetic idea relies on the construction of two rings (beta-lactone and pyrrolidinone). The formation of the spiro-beta-lactone was accomplished by a crossed Cannizzaro reaction, while the 3,4-disubstituted pyrrolidinone ring was constructed by a titanium(IV) chloride mediated chelation-controlled double stereodifferentiating Crimmins aldol reaction of Garner's aldehyde.
Keywords: Crimmins aldol reaction; crossed Cannizzaro reaction; Garner's aldehyde; lactones; Mitsunobu reaction; pyrrolidine

Concise synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate - Ramalingam, S.; Bhise, Ankushkumar D.; Show, Krishanu; Kumar, Pradeep (Arkivoc, 2013)
An efficient synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate 1, a common intermediate for various polyhydroxylated piperidines is reported in six steps with 32% overall yield starting from Garner's aldehyde. The key steps include the diastereoselective nucleophilic addition and intramolecular cyclization. (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate is a common precursor for the synthesis of 1-deoxy-L-mannojirimycin, 1-deoxy-L-idonojirimycin, L-fagomycin and related analogues.
Keywords: cyclization; Garner's aldehyde; nucleophilic addition; polyhydroxy piperidines